Isolation of fungal pathogens from eggs of the endangered sea turtle species Chelonia mydas in Ascension Island. (5th December 2016) - Sarmiento-Ramirez, Jullie M.; Sim, Jolene; Van West, Pieter; Dieguez-Uribeondo, Javier
Abstract : Fungal emerging pathogens are one of the main threats for global biodiversity. Sea turtles do not seem to be an exemption, and recent studies on important nesting areas worldwide have shown that two fungal pathogens, i.e. Fusarium falciforme and Fusarium keratoplasticum, are involved in low hatching success in nests of sea turtle species. Although the presence of these pathogens has been detected in Ascension Island, there are no investigations on the distribution of these two pathogens in main nesting beaches in the island. In this study, we analysed 109 eggshells of the species Chelonia mydas from four nesting areas in Ascension Island. We have isolated and identified a total of 46 fungal isolates. A phylogenetic analysis, of the ITS nrDNA region, with a number of reference sequences of the Fusarium solani species complex, showed that 23 of these isolates corresponded to the pathogen F. keratoplasticum . The analyses on isolation frequency, that included other previously obtained isolates, i.e. 11 F. keratoplasticum and one F. falciforme, showed that F. keratoplasticum was the species most frequently isolated in Ascension Island and it was found in all nesting beaches, while F. falciforme was only isolated from Pan Am beach. When compared with other nesting areas worldwide, the abundance of F. keratoplasticum over F. falciforme was higher than any other nesting region tested. These findings are important in order to evaluate the potential threat of this pathogen to nests of the sea turtle population of Ascension Island, and to develop future control strategies.